IMPLEMENTASI KEWAJIBAN DAN HAK SUAMI ISTRI DI PAUD IT AL-HASANAH KELURAHAN PAGAR DEWA KOTA BENGKULU - Nurhasanah, Nurhasanah (UIN Fatmawati Sukarno Bengkulu, 2022)
Abstract: The formulation of the problem in this study are: 1) How is the obligations and rights of husband and wife in PAUD IT Al-Hasanah 2) How is the implementation of the mubadalah concept regarding the obligations and rights of husband and wife in PAUD IT Al-Hasanah, Pagar Dewa Village, Bengkulu City. This type of research is a research that focuses on qualitative data from the field (field research). Data collection techniques that researchers use are observation, interviews, and documentation. Data analysis uses gender equality theory, structural-functional theory, and mubadalah. This study concludes that: 1) The implementation of the obligations and rights of of husband and wife in PAUD IT Al-Hasanah consists of two forms, namely implemented and not implemented. 2) The implementation of the mubadalah concept in the obligations and rights of husband and wife in PAUD IT Al-Hasanah are mostly mubadalah. The structural and functional aspects have been implemented properly. The husband has carried out his duties as a breadwinner as well as helping with domestic tasks, the wife has carried out her duties as a mother and wife as well as a career woman who helps the family economy. The concept of gender equality between husband and wife has also been implemented well. Husband and wife have carried out their functions and have worked together. Keywords: Obligations and Rights, Husband and Wife, Mubadalah. Abstrak: Rumusan masalah dalam penelitian ini adalah: 1) Bagaimana pelaksanaan kewajiban dan hak pasangan suamiistri di PAUD IT Al-Hasanah ? 2) Bagaimana implementasi konsep mubadalah dalam kewajiban dan hak suami istri di PAUD IT Al-Hasanah Kelurahan Pagar Dewa Kota Bengkulu? Jenis penelitian ini adalah penelitian yang memfokuskan data dari lapangan (field research) kualitatif.Teknik pengumpulan data yang peneliti gunakan adalah dengan observasi, wawancara, dan dokumentasi.Analisis data menggunakan teori kesetaraan gender, teori struktural-fungsional, dan mubadalah. Penelitian ini menyimpulkan bahwa: 1) Pelaksanaan kewajiban dan hak suami-istri di PAUD IT Al-Hasanah mayoritas sudah dilaksanakan bersama oleh suami dan istri. 2) Implementasi konsep mubadalah dalam kewajiban dan hak suami istri di PAUD IT Al-Hasanah mayoritas sudah mubadalah. Dengan demikian aspek struktural dan fungsional sudah diterapkan dengan baik. Suami sudah menjalankan tugasnya sebagai pencari nafkah sekaligus membantu tugas domestik, istri menjalankan tugasnya sebagai ibu dan istri sekaligus wanita kariryang membantu ekonomi keluarga. Konsep kesetaraan gender antara suami dan istri juga sudah diterapkan dengan baik. Suami dan istri sudah menjalankan fungsinya dan sudah saling bekerja sama. Kata kunci: Kewajiban dan Hak, Suami Istri, Mubadalah